Penerapan Akuntansi Persediaan Barang Dagang pada UD Prapatan Motor Kudus - Rakhmawati, Ita (AKTSAR: Jurnal Akuntansi Syariah, 2019)
Merchandise inventory is one account that has significant values and functions. The amount of inventory must not be too much because it will affect to liquidity. However, it should not be too small because it will eliminate potential of revenue from customers. This research aim to whether the accounting treatment of good inventory methods on Prapatan Motor Entreprise. This research uses qualitative approach, The types of data collected are primary and secondary data. This study related of recording, assessment, and reporting of finished goods inventory . This study concludes Prapatan Motor Entreprise have execute an accounting inventory process. The company use physical recording methods and average methods on inventory assesment.on the end of accounting period, Inventory present on financial position and cost of production report. But the company don’t have inventory control card so must stock opname periodically.